Healthcare providers' perceptions of the kidney transplant program at King Faisal Hospital Rwanda: A one-year evaluation. - Marissa Martinelli; Emile Twagirumukiza; Ahmed M Elbasha; Augustin Sendegeya; Belise S Uwurukundo; Jules Karangwa; Kara L Neil; Laetitia Nshimiyimana; Jeffrey Punch (PLOS Global Public Health)
The living donor kidney transplant program was established at King Faisal Hospital Rwanda (KFH) in 2023, to reduce medical abroad referrals and strengthen the health care delivery system. The study aimed to explore healthcare provider perspectives, their needs for further developing the kidney transplant program at KFH and provide recommendations to fill these gaps. This study employed a sequential explanatory mixed methods approach embedded within an overarching exploratory research design, collecting data from healthcare workers who participated in at least one kidney transplant mission at KFH since 2023. Participants represented the dialysis, outpatient renal clinics, operating theatres, and postoperative kidney transplant units. Data were collected through initial surveys, which informed the semi-structured interviews. Descriptive and thematic analyses of the results were performed. The study included 50 respondents. 32% of respondents were extremely satisfied with the devices, infrastructure, and technology used in kidney transplantation at KFH, while also positing that missing or non-functional devices limit their ability to care for kidney transplant patients. 11 healthcare providers were interviewed. The most reported strength of the program was effective governance and management systems, while the areas needing improvement were education and training, patient care coordination, infrastructure, instruments, and devices. The findings of this study underscore the importance of strong political and institutional will, hospital organization, and multidisciplinary team collaboration in sustaining renal transplantation programs. Participants recommended practical-based training, rotations into high-volume facilities, and regular refresher training. Early renal disease diagnosis and ensuring treatment affordability were also recommended.